Pengembangan Sistem Pengelolaan Ruang Baca Berbasis Web Dengan Menggunakan Django Framework (Studi Kasus: Ruang Baca Fakultas Ilmu Komputer Universitas Brawijaya) - Atikah Nur Rahimah; Denny Sagita Rusdianto; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Brawijaya University has one central library and several smaller libraries in each of its faculties, including a library located in the Faculty of Computer Science which is commonly called a Reading Room. Currently, Reading Room management is done by using an open source software called Senayan Library Management System (SLIMS). The use of SLIMS is deemed not quite helpful because the membership system cannot be connected with the student database that is owned by the faculty which make it difficult to check the students's status when they are going to make transactions. In addition, the Reading Room does not have collection data, especially thesis, to be seen by students online, making it difficult for students who want to find data outside of the Reading Room's working hours. As a solution, a web-based Reading Room Management System was developed. This system has features for managing collection data and reading room transactions with member data that is integrated with the faculty. In addition, this system can be used by students to search collection data including thesis data online. This research begins with requirements engineering process that produces 59 functional requirements and 1 non-functional requirement. Then, the system design is carried out. The implementation is done using Django framewok. From the testing process, the results are 100% valid for unit testing, integration, and validation. As for usability testing, the value of 82.92 means that the Reading Room Management System falls into the 'A'.